Analysis of the life stages of Cimex lectularius captured within a medical centre suggests that the true numbers of bed bug introductions are under-reported. Issue 3 (November 2017) - Sheele, J.M.; Barrett, E.; Dash, D.; Ridge, G.E.
Summary: Little is known about the epidemiology of bed bugs within the healthcare system, but nymphal stages predominate in natural infestations. This study determined the life stages of bed bugs captured within a medical centre, and found that older bed bugs were more likely to be captured than younger insects. The numbers of first instars, third–fifth instars and adult females captured were significantly different compared with the numbers of each life stage found in a natural infestation ( P <0.01). A significant number of early-instar bed bugs introduced into the medical centre may go unnoticed by hospital staff.